2017
DOI: 10.13057/biodiv/d180213
|View full text |Cite
|
Sign up to set email alerts
|

The inventory of edible mushroom in Kamojang Nature Reserve and Nature Park, West Java, Indonesia

Abstract: Research on the potential of macroscopic fungi in the forests of Indonesia as food and medicine still hasn't much been done. Until now, the biodiversity data of macroscopic fungi are destitute. On the other hand, we are faced with the rapid rate of decline of biodiversity both by natural processes and by human activities. The purpose of this study was to determine the species of edible mushroom in Kamojang Natural Reserves and Nature Park, Bandung-Garut Districts, West Java. The method used in this research we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 55 publications
(17 reference statements)
0
9
0
4
Order By: Relevance
“…Several previous studies have confirmed the existence of Stereum in Sukabumi (Triastinurmiatiningsih et al 2017); Stereum cf. Pergameneum which is a new record Sumatra Island (Susan & Retnowati, 2018); 3 species of Stereum from Kamojang, West Java Tourist Park (Arko, Marzuki, & Kusmoro, 2017); source of sterostreins (Isaka et al, 2011); antifungal activity (Aqueveque et al, 2017) and the potential of Stereum as drugs in the Kepulauan Seribu (Noverita et al, 2019).…”
Section: Stereum Spmentioning
confidence: 99%
“…Several previous studies have confirmed the existence of Stereum in Sukabumi (Triastinurmiatiningsih et al 2017); Stereum cf. Pergameneum which is a new record Sumatra Island (Susan & Retnowati, 2018); 3 species of Stereum from Kamojang, West Java Tourist Park (Arko, Marzuki, & Kusmoro, 2017); source of sterostreins (Isaka et al, 2011); antifungal activity (Aqueveque et al, 2017) and the potential of Stereum as drugs in the Kepulauan Seribu (Noverita et al, 2019).…”
Section: Stereum Spmentioning
confidence: 99%
“…Species belonging genus Phlebia rarely are considered to be edible or medicinal mushrooms. However, some reports have recently mentioned about its edible or medicinal properties [18,19]. Figure 2.…”
Section: Effects Of Substrates On the Growth And Yield Of Fruiting Bomentioning
confidence: 99%
“…As many as 200,000 species from 1.5 million species of mushrooms are estimated to be found in Indonesia. Many fungi biodiversity has been documented in many national park around Indonesia such as kamojang (Arko, 2017), Gunung Halimun (Putir, 2019) and many more. Information about fungi on Baluran revealed the diversity of endophytic one on evergreen area (Murdiyah, 2017).…”
Section: Introductionmentioning
confidence: 99%